THE TRANSFORMATION OF RETAIL INVESTOR BEHAVIOR IN INDONESIA’S CAPITAL MARKET: BETWEEN THE TREND OF DIGITALIZATION AND FINANCIAL LITERACY - Dewi, Putu Eka Dianita Marvilianti; Wahyuni, Made Arie; Dewi, Gusti Ayu Ketut Rencana Sari; Dewi, Luh Gede Kusuma; Savitri, Ni Luh Asri (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The main objective of this article is to analyze the transformation of retail investor behavior in Indonesia's capital market in the context of digitalization and financial literacy. The background problem lies in the rapid increase of individual investors, which is not always accompanied by rational investment decision-making, especially amidst the widespread use of digital trading platforms and exposure to social media. The novelty of this study lies in its integrated approach, combining perspectives from technology, behavioral psychology, and financial literacy to understand investment decision dynamics an approach that remains limited in the context of emerging markets like Indonesia. The research method employed is a descriptive qualitative analysis based on secondary data and literature from authoritative sources such as the Financial Services Authority (OJK), KSEI, and recent academic studies. The findingsindicate that digitalization expands access to investment but simultaneously increases susceptibility to psychological biases such as herding behavior and overconfidence, especially when not balanced with sufficient financial literacy. The conclusion suggests that experiential financial education and adaptive regulations are crucial for building an inclusive and sustainable capital market.